2022
DOI: 10.1002/anie.202205946
|View full text |Cite
|
Sign up to set email alerts
|

Ru–Co Pair Sites Catalyst Boosts the Energetics for the Oxygen Evolution Reaction

Abstract: Manipulating the coordination environment of the active center via anion modulation to reveal tailored activity and selectivity has been widely achieved, especially for carbon-based single-atom site catalysts (SACs). However, tuning ligand fields of the active center by single-site metal cation regulation and identifying the effects on the resulting electronic configuration is seldom explored. Herein, we propose a single-site Ru cation coordination strategy to engineer the electronic properties by constructing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
145
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 253 publications
(146 citation statements)
references
References 69 publications
1
145
0
Order By: Relevance
“…As depicted in Figure b, the Ru K-edge XANES spectra confirmed the changes in the oxidation state of Ru in Ru NPs/NC. Specifically, with the increase of the N content and electron transfer at the interface, the absorption edge shifted to the lower energy direction, and the peak of the white line gradually decreased, indicating the decrease of the valence state . In Figure c, EXAFS oscillations of Ru NPs/NC exhibited smaller amplitudes than that of Ru foil due to the finite size effect of metal nanoparticles .…”
Section: Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As depicted in Figure b, the Ru K-edge XANES spectra confirmed the changes in the oxidation state of Ru in Ru NPs/NC. Specifically, with the increase of the N content and electron transfer at the interface, the absorption edge shifted to the lower energy direction, and the peak of the white line gradually decreased, indicating the decrease of the valence state . In Figure c, EXAFS oscillations of Ru NPs/NC exhibited smaller amplitudes than that of Ru foil due to the finite size effect of metal nanoparticles .…”
Section: Results and Discussionmentioning
confidence: 90%
“…Specifically, with the increase of the N content and electron transfer at the interface, the absorption edge shifted to the lower energy direction, and the peak of the white line gradually decreased, indicating the decrease of the valence state. 45 In Figure 2c, EXAFS oscillations of Ru NPs/NC exhibited smaller amplitudes than that of Ru foil due to the finite size effect of metal nanoparticles. 46 Moreover, the slightly longer periods of Ru NPs/NC-900 than that of Ru NPs/NC-800 and Ru NPs/NC-1000 were attributed to shorter distances between central Ru atoms and surrounding coordinated Ru atoms, indicating the lattice compressive strain of NPs.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…However, to the best of our knowledge, the rare-earth M–N 4 moiety with coordination unsaturated metal atoms exhibits high absorption electrocatalysis, which has not been explored yet in battery systems. Given numerous degrees of freedom for adjusting the metal center and local atomic environments of single-atom catalysts, a conventional trial-and-error strategy significantly slows down the development of SACs in electrochemical energy storage and conversion. , Therefore, more efforts should be made for a more advanced and efficient design strategy of rare-earth metal-based single atoms in Na–S battery applications.…”
Section: Introductionmentioning
confidence: 99%
“…Given numerous degrees of freedom for adjusting the metal center and local atomic environments of single-atom catalysts, a conventional trial-and-error strategy significantly slows down the development of SACs in electrochemical energy storage and conversion. 39,40 Therefore, more efforts should be made for a more advanced and efficient design strategy of rare-earth metal-based single atoms in Na−S battery applications.…”
Section: Introductionmentioning
confidence: 99%
“…The band gap of Ru 1 /V Co -Co­(OH) 2 was 0.26 eV, which was narrower than that of Ru 1 /Co­(OH) 2 (0.62 eV). The narrower band gap of Ru 1 /V Co -Co­(OH) 2 indicated that the existence of neighboring Co 2+ vacancies enhanced the electronic conductivity, which facilitated charge transfer and OER dynamics. …”
Section: Results and Discussionmentioning
confidence: 99%